Advancing string theory with 4G model of final unification - U.V. Satya Seshavatharam; S. Lakshminarayana; T. Gunavardhana Naidu (Journal of Physics: Theories and Applications, 2025)
In the framework of the recently proposed 4G model of final unification, integrating three large atomic gravitational constants corresponding to the electromagnetic, strong, and electroweak interactions, we explore the physical existence of a fundamental electroweak fermion of rest energy ≈ 585 GeV. This particle is envisioned as the “zygote” of all elementary fermions and as the weak‐field counterpart to photons and gluons. Using three core assumptions and five defining relations, the model quantitatively reproduces key nuclear and particle physics observables, including the strong coupling constant, nuclear binding energies, neutron lifetime, charge radii, and several dimensionless large numbers. Theoretical string tensions and energies are derived for each atomic interaction (weak, strong, electromagnetic) using experimentally relevant scales (GeV–MeV–eV) rather than the inaccessible Planck scale, thus extending string theory’s applicability to testable low‑energy domains. Comparative analysis (Tables 1 and 2) demonstrates close agreement between calculated string energies and known interaction energies, providing a bridge between quantum gravity concepts and measurable nuclear data. The model also predicts possible astrophysical signatures of the 585 GeV fermion through annihilation and acceleration processes capable of generating TeV–multi‑TeV photons. While the approach is qualitative in some mathematical details, its ability to fit fundamental constants and nuclear properties within a unified string–gravitational paradigm offers a promising, experimentally approachable route toward a physically grounded final unification theory.